Development and validation of a new teaching framework for teacher educators in Malaysian higher teacher education institutions - Rosdy Wahid (2019)
This study aimed to develop and validate a new teaching framework for teacher educators in Malaysiausing an exploratory mixed-method study design. A qualitative phase involved document analysis oftheories, principles and policies underlies teaching framework of selected teachereducation institutions and interviews with 10 stakeholders namely two policy makers, twoteacher educators, four teacher mentors and two Ministry of Education personnel in Malaysia. Inthis phase, six constructs or factors emerged, namely (i) Intellectual Excitement (IE); (ii)Quality Learning Spaces, Resources and Technology (QL); (iii) Constructive Alignment (CA);(iv) International and Cultural Diversity (IC); (v) Climate of Inquiry and Critical Reflection(CR); and (vi) Good Values, Attitudes and Behaviour (GV). In a quantitative phase, a 67-itemquestionnaire was developed based on the themes under each construct and administered to 248teachers using the stratified random sampling. The analysis using Exploratory Factor Analysisretained the six factors which were clustered thematically to 14 sub-constructs accordingto the factor loading. This 14 sub-construct questionnaire was again administered to toa different set of 458 teachers in the high- performance schools selected using thestratified random sampling method. Analysis using Confirmatory Factor Analysis (CFA) by means ofMeasurement Model with the goodness- of-fit value (GFI0.90), Construct Reliability value(CR0.6) and Average Variance Extracted value (AVE0.5) further confirmed the six factors,retaining the 14 sub-constructs which constituted the Teaching Framework for Teacher Educators(MyTF@TE). A closer inspection of MyTF@TE indicated that the first four sub-constructs(group discussion, critical thinking, evaluating peers work and knowledge transfer) were derivedfrom IE, three sub-constructs (learning resources, physical setting, and technology integration)from QL, two sub-constructs (learning outcome and theory to practice) from CA, two sub-constructs(global connection and embracing culture diversity) from IC, and two sub-constructs(welcoming ideas and improving practices) from CR. Meanwhile, GV stood alone as the sub-construct.As a conclusion, Teacher Framework for Teacher Educators (MyTF@TE) based on the 14 factors wasvalidated through the EFA and further confirmed through the CFA. The implication of the findings isthat the factors embodied in a visual guideline may isting and uplifting the quality of teachereducators across the MalaysianHigher Teacher Education institutions.